Human Relations With Other Humans According to Burhan Nurgiyantoro in Novel ‘Sepasang yang Melawan 2’ by Jazuli Imam Approaches to Literary Sociology - M. Nur Wakhid Ubaidillah A.; Alfian Setya Nugraha (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
The purpose of this study is to analyze moral values with one of the concepts of moral values by Dr. Burhan Nurgiyantoro, namely the relationship between humans and other humans and their environment in the novel Pair of Resisting 2 by Jazuli Imam. According to Dr. Burhan Nurgiyantoro there are 3 concepts of moral values, (1) Man's relationship with himself, (2) Man's relationship with other humans and their environment, (3) Man's relationship with his god. This study focuses on the second concept. This research is a type of qualitative research and uses content analysis. The approach used is the approach of literary sociology. This study found 4 moral values of human relationships with other humans, these values are in the form of help, empathy, compassion and care for others or strangers.